Systemic inflammatory response syndrome–related lymphopenia is associated with adenosine A1 receptor dysfunction. Issue 1 (11th May 2017) - Riff, Reut; Cohen, Yair; Eini‐Rider, Hadar; Naamani, Oshri; Mazar, Julia; Haviv, Yosef S.; Chaimovitz, Cidio; Douvdevani, Amos
Abstract : In SIRS, adenosine elevation desensitizes its Gi‐coupled A1 receptor, an effect associated to cAMP elevation and lymphopenia. Abstract : SIRS is associated with lymphopenia, and prolonged lymphopenia of septic patients has been associated with increased mortality risk. We hypothesize that elevated adenosine during SIRS down‐regulates Gi ‐coupled A1 R, which signals an effect that sensitizes a cAMP‐dependent lymphotoxic response. In this study, we evaluate the role of adenosine in SIRS‐mediated lymphopenia and impaired IL‐15 production. Cecal ligation and puncture was used to induce sepsis‐associated SIRS in mice. BMDCs were cultured and used to measure the effect of adenosine on IL‐15. We found that A1 R mRNA levels were significantly down‐regulated and A1 R‐dependent Gi activity was abolished in T cells of septic mice. In accordance, cAMP was elevated in isolated T cells from cecal ligation and puncture compared with sham‐treated mice. Similar to septic mice, leukopenia was evident in sham A1 R‐KO mice, after treatment with the A1 R antagonist (8‐cyclopentyl‐1, 3‐dipropylxanthine), or after A1 R desensitization. In contrast, A2A R‐KO mice were protected from leukopenia. In addition, we observed that septic A1 R‐KO mice exhibited low IL‐15 levels. Cultured BMDC agonists of A2A R and A2B R inhibited IL‐15 production and adenosine blocked IL‐15–dependent proliferation of cytotoxic T cells that were cocultured with stimulated BMDCs. To conclude, we suggest that SIRS‐associated lymphopenia is initiated by A1 R desensitization and adenosine‐mediated inhibition of IL‐15 production is part of the mechanism that accounts for the delay in leukopenia recovery in patients with severe sepsis. Interference with adenosine signaling may thus be potentially beneficial for septic patients with leukopenia.